2015
DOI: 10.3892/ijo.2015.3191
|View full text |Cite
|
Sign up to set email alerts
|

Loss of autophagy-related protein Beclin 1 may define poor prognosis in ovarian clear cell carcinomas

Abstract: The aim of the present study was to clarify the role of autophagy in cisplatin (CDDP) sensitivity in OCCCs and the role of Beclin 1 in OCCC progression. Autophagy was measured using: i) western blot analysis of LC3 and p62 and ii) microscopic observation of GFP-LC3 puncta. Autophagy was suppressed using chloroquine and Beclin 1 siRNA. Surgical specimens were examined for Beclin 1 protein expression by immunohistochemistry. The correlations between the loss of Beclin 1 expression and clinicopathological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
0
22
0
2
Order By: Relevance
“…Autophagy is related to a variety of autophagy-related genes, among which LC3 and Beclin1 are important autophagic factors (15). LC3, as a homologous gene with autophagy-related gene Atg8 in yeast, and a specific marker of autophagosome, which expression level can directly reflect the level of autophagy (16).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is related to a variety of autophagy-related genes, among which LC3 and Beclin1 are important autophagic factors (15). LC3, as a homologous gene with autophagy-related gene Atg8 in yeast, and a specific marker of autophagosome, which expression level can directly reflect the level of autophagy (16).…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 This type of cell death is defined as type II programmed cell death, or autophagic cell death, and deregulation of this process can lead to changes in cell homeostasis, resulting in tumorigenesis. 13 Therefore, it is essential to determine the underlying molecular mechanisms of autophagy in ovarian cancer, which may be helpful for early detection, diagnosis and treatment.…”
mentioning
confidence: 99%
“…It was demonstrated that the expression levels of beclin 1, p62 and ATG5 protein in T24 cells were decreased in a dose-dependent manner following treatment with MMC and increasing 5-Aza-CdR concentrations. Beclin 1, p62 and ATG5 are considered as the key regulators of autophagic cell death (14)(15)(16). Autophagy is a lysosome-dependent self-digesting system primarily responsible for the removal and recycling of long-lived proteins, and damaged or obsolete intracellular organelles, in order to maintain cell homeostasis (17).…”
Section: Discussionmentioning
confidence: 99%